2016
DOI: 10.1007/s11356-016-7146-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of juvenile Solea solea as sentinel in the marine platform of the Ebre Delta: in vitro interaction of emerging contaminants with the liver detoxification system

Abstract: Juveniles of Solea solea were sampled during the spring season in three consecutive years at a marine site by the mouth of the Ebre river. The aim was to assess if the extractive works from the toxic load upstream the river could be reflected on the health status of the fish living at the immediate sea. The biomarkers selected for the in vivo field study are commonly used as indicators of chemical exposures. They include activities of energy metabolism: lactate dehydrogenase (LDH) and citrate synthase (CS); ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 43 publications
2
15
1
Order By: Relevance
“…The results showed that Se was higher in the liver of fish fed dietary Se at 1 mg/kg comparing to the other levels, but this level is comparable with other previous studies. The liver tissue is responsible for the detoxification of external agents that probably impair the health of fish ( Crespo and Solé, 2016 ). Therefore, the increased level of Se in the liver of Striped catfish is associated with liver function to regulate Se level in the entire body.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that Se was higher in the liver of fish fed dietary Se at 1 mg/kg comparing to the other levels, but this level is comparable with other previous studies. The liver tissue is responsible for the detoxification of external agents that probably impair the health of fish ( Crespo and Solé, 2016 ). Therefore, the increased level of Se in the liver of Striped catfish is associated with liver function to regulate Se level in the entire body.…”
Section: Discussionmentioning
confidence: 99%
“…All assays were carried out in triplicate at 25°C, except 7-ethoxyresorufin O-deethylase (EROD) and 7-benzyloxy-4-[trifluoromethyl]-coumarin-O-debenzyloxylase (BFCOD), which were at 30°C, in 96-wellplates using a TECAN Infinite M200 microplate reader (Salzburg, Austria). A detailed description of this multi-biomarker approach has been recently detailed elsewhere (Crespo and Solé 2016). Briefly, EROD and BFCOD activities were measured using 50 µl of undiluted liver homogenate samples (S10) with a reaction mixture containing: 0.2 mM NADPH, 3.3 µM 7-ethoxyresorufin (ER) or 0.02 mM NADPH and 200 µM BFC in 100 mM phosphate buffer (pH 7.4).…”
Section: Site Characterisation By the Use Of Fish Biomarkersmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report on CbE induction by these two pharmaceutical drugs in fish although an induction by other drugs such as gemfibrozil, nonylphenol, and ethinylestradiol was formerly reported in vivo in the same fish species [31]. IBU and CBZ have also revealed to inhibit in vitro microsomal CbE activity in several marine species [28], and the lipid regulators simvastatin and fenofibrate interfere in vitro with microsomal CbE of either adults or juveniles of a related species Solea solea [28,32]. Due to the importance of this enzyme family in drug and prodrug metabolism as well as its endogenous role in lipid homeostasis, we recommended its potential use as marker of drug exposures.…”
Section: Biological Effects On Detoxification Enzymesmentioning
confidence: 73%